ESTIMATION OF STRUCTURE AND PERMEABILITY ZONE BASED ON RELOCATED HYPOCENTER OF MICROEARTHQUAKECASE STUDY AT PATUHA GEOTHERMAL FIELD - Berrizki Hermawan, Irfan
Generally, analysis of structure and permeable zones in geothermal field is carried out using remote sensing methods, direct mapping to the field, and analysis of gravity data. These methods can provide the distribution of structure in the field but cannot provide information whether the structure is active or not. This study aims to utilize microearthquake events with improved hypocenter accuracy to obtain hypocenter distribution with a certain trend and can be used for more accurate interpretation of geological structures and permeable zones. Improvement of hypocenter position is carried out using the Double-Difference method and additional input from Waveform Cross-Correlation (WCC) to obtain adjacent earthquake pairs with similar waveforms. The processing results show that there are 3 earthquake clusters formed, namely in the western, central, and eastern parts of the Ciwidey-Patuha Geothermal System. The western cluster show 2 orientations of conjugated hypocenter distribution which supports the indication of upflow zone in the western area of Ciwidey-Patuha Geothermal System. The low Vs anomaly formed in this area supports an indication of fluid present in the western area. The middle cluster formed coincides with the reservoir zone of Mount Urug. The results of the multiplet clustering analysis indicate 2 different source mechanisms operating in the reservoir zone. The tomographic results show a low Vp/Vs anomaly in the area of Mount Urug indicates microdiorite or andesitic rocks with high silica content which causes of separated fluid flow of reservoir towards the production wells in the west and Ciwidey-Crater Geothermal System in the east. Integration of all data supports an indication of upflow zone in the western part of the Ciwidey-Patuha Geothermal System and presence of microdiorite or andesitic rock with high content silica which separates geothermal fluid flows reservoir Mount Urug toward the production well zone in the west and the Ciwidey-Crater Geothermal System in the east.